2019
DOI: 10.3389/fonc.2019.00731
|View full text |Cite
|
Sign up to set email alerts
|

Carbon-ion Radiotherapy for Isolated Lymph Node Metastasis After Surgery or Radiotherapy for Lung Cancer

Abstract: Purpose: Mediastinal and hilar lymph node metastasis is one of the recurrence patterns after definitive treatment of lung cancer. Salvage radiotherapy (RT) can be a treatment option for lymph node metastasis. However, the usefulness of additional RT remains unclear after surgery or RT for the primary lung tumor. We retrospectively evaluated the efficacy and safety of hypofractionated carbon-ion RT for isolated lymph node metastasis. Methods and Materials: Between April 2013 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Another current barrier to adoption in the United States is the lack of current randomized data to suggest a benefit of CIRT, although the development of a CIRT center in the United States has the potential to further develop new protocols and to advance preclinical research. Currently, early clinical prospective and retrospective studies have suggested both the safety and the efficacy of CIRT for a variety of disease sites, although there remains few phase III protocols [48][49][50][51][52][53][54][55][56][57][58][59][60]. Based on those early studies, multiple protocols are currently enrolling patients internationally [61].…”
Section: Discussionmentioning
confidence: 99%
“…Another current barrier to adoption in the United States is the lack of current randomized data to suggest a benefit of CIRT, although the development of a CIRT center in the United States has the potential to further develop new protocols and to advance preclinical research. Currently, early clinical prospective and retrospective studies have suggested both the safety and the efficacy of CIRT for a variety of disease sites, although there remains few phase III protocols [48][49][50][51][52][53][54][55][56][57][58][59][60]. Based on those early studies, multiple protocols are currently enrolling patients internationally [61].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, as for conventional RT, fPRT or single-dose PRT might greatly affect the synergistic potential between PRT and IO, as already demonstrated for combined PRT and targeted therapies [ 194 , 195 ]. PRT fractionation thus far has shown excellent local control without severe toxicities [ 196 , 197 , 198 ]. For the radiobiology of protons and carbon ions, we refer to excellent reviews [ 199 , 200 , 201 , 202 , 203 ].…”
Section: Charged Particle Radiotherapymentioning
confidence: 99%
“…Mediastinal and hilar LNM is one of the recurrence patterns after definitive treatment of lung cancer. 4 Lymph node dissection is an important part of this procedure that can improve the prognosis of the patients diagnosed with early stage. 5 Although radiotherapy has proven to be effective for LNM, radiation pneumonitis inevitably decreases patients’ performance status and quality of life, which can be related to a worse long-term prognosis.…”
Section: Introductionmentioning
confidence: 99%
“… 7 Especially, repeated radiotherapy for lymph node recurrence after primary tumors should be evaluated carefully, because irradiation areas are wide and an excess radiation dose can be caused by overlapping radiotherapy. 4 , 8 Additionally, hilar and mediastinal lymph node metastases are frequently located close to organs at risk. 4 Therefore, it is an urgent need to develop an accurate model for predicting the risk of LNM that can be used to facilitate the management of clinical treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation